Pengelolaan Keuangan UMKM Makanan di Kecamatan Kubung Kabupaten Solok Ditinjau dari Pengetahuan dan Perilaku Keuangan - Seflidiana Roza; Eka Hendrayani; Marta Linda (MAMEN: Jurnal Manajemen, 2026)
This research aims to evaluate the financial management practices of food sector SMEs in Kubung Subdistrict, Solok Regency, by examining the financial literacy and financial behavior of SME operators. Adopting a quantitative approach within an explanatory research framework, the study targeted a population of 280 SMEs and selected a sample of 45 using purposive sampling. Data were obtained via questionnaires and document analysis, then subjected to multiple linear regression analysis. The results reveal that financial literacy has no significant partial effect on financial management (t_calculated = 1.498 < t_table = 2.019; p = 0.142 > 0.05), whereas financial behavior exerts a significant partial influence (t_calculated = 2.874 > t_table = 2.019; p = 0.006 < 0.05). Simultaneously, financial literacy and financial behavior significantly impact financial management (F_calculated = 26.797 > F_table = 3.23; p = 0.000 < 0.05). The coefficient of determination test (R² = 0.567) indicates that these two independent variables explain 56.7% of the variation in financial management, with the remaining 43.3% influenced by other factors outside the scope of this study.